2023
DOI: 10.3389/fphar.2023.1226647
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tacrolimus conversion from immediate- to extended-release formulation on renal function in renal transplant patients: a meta-analysis

Sheng Chao,
Lei Jia,
Kejing Zhu
et al.

Abstract: Objective: Tacrolimus formulation affects the outcomes of a renal transplant, while the effect of its immediate- to extended-release conversion remains controversial. This meta-analysis aimed to compare the renal function before and after tacrolimus immediate- to extended-release conversion in renal transplant patients.Methods: PubMed, Cochrane, Embase, CNKI, CQVIP, and Wanfang databases were searched for articles regarding the effect of tacrolimus conversion from immediate- to extended-release formulation on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The use of prolonged- or extended-release formulations of tacrolimus, usually taken once a day, is a part of the clinical standard of care for kidney transplant recipients ( 1 ). Recently, a meta-analysis indicated that the conversion from IR-Tac twice daily to ER-Tac once daily may decrease serum creatinine in kidney transplant recipients with a follow-up duration of more than 48 weeks, but at the same time, eGFR remained unchanged ( 11 ). At least many randomized controlled studies could show that the administration of ER-Tac once daily with less peak levels (and therefore in total reduced maximum plasma concentrations) does not appear to have an impact on either the efficacy or safety of this formulation and is an effective immunosuppressant treatment in kidney transplant recipients ( 7 , 8 , 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of prolonged- or extended-release formulations of tacrolimus, usually taken once a day, is a part of the clinical standard of care for kidney transplant recipients ( 1 ). Recently, a meta-analysis indicated that the conversion from IR-Tac twice daily to ER-Tac once daily may decrease serum creatinine in kidney transplant recipients with a follow-up duration of more than 48 weeks, but at the same time, eGFR remained unchanged ( 11 ). At least many randomized controlled studies could show that the administration of ER-Tac once daily with less peak levels (and therefore in total reduced maximum plasma concentrations) does not appear to have an impact on either the efficacy or safety of this formulation and is an effective immunosuppressant treatment in kidney transplant recipients ( 7 , 8 , 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%